FAKTOR-FAKTOR YANG MEMPENGARUHI KINERJA PERUSAHAAN YANG TERDAFTAR DI BEI PERIODE 2016-2018 - Thomas Adrian, Viriany (Jurnal Paradigma Akuntansi, 2020)
The purpose of this research is to examine the effect of liquidity, financial leverage, and firm size on firm performance of manufacturing company listed on Indonesia Stock Exchange (IDX) during period 2016-2018. The sample used is 72 companies. The results showed that liquidity variable has significant negative impact on firm performance, financial leverage variable has insignificant positive impact on firm performance, and firm size variable has insignificant negative impact on firm performance.